Analysis of Meiotic Segregation Patterns and Interchromosomal Effects in Sperm from 13 Robertsonian Translocations - Wang, B (Balkan J Med Genet, 2017)
The frequency of the Robertonian (ROB) translocation in newborn babies is approximately one in 1000. Robertsonian translocation is an unusual type of chromosome rearrangement caused by two particular chromosomes joining together. The aim of the study was to analyze the segregation of the ROB translocations in 13 male carriers, and to verify a possible inter-chromosomal effect (ICE) of the ROB translocation on chromosomes 18, X, and Y. Thirteen male patients were included in the study. Multicolor fluorescent in situ hybridization (FISH) was used to analyze chromosomes 13, 14, 15, 21, 22, 18, X and Y in sperm. Among the heterozygous ROB translocation carriers, the frequency of normal/balanced spermatozoa resulting from alternate segregation varied between 70.4 and 85.2%. The frequency of unbalanced spermatozoa resulting from adjacent segregation varied between 14.8 and 29.6%. Increased frequencies of aneuploidy for a sex chromosome were found in 10 ROB translocation carriers (P2-P8, P10-P12). Increased frequencies of aneuploidy for chromosome 18 were found in10 ROB translocation carriers (P3-P9, P11-P13). In addition, increased frequencies of diploid were found in 11 ROB translocation carriers (P2-P9, P11-P13). Among the homozygous ROB translocation carriers, the rate of balanced spermatozoa was 99.7% and the frequency of unbalanced spermatozoa was 0.3%. However, the frequencies of aneuploidy for a sex chromosome and chromosome 18 were normal. Despite the high number of normal/balanced frequencies, there remained many unbalanced spermatozoa resulting from alternate segregation. The ROB translocation carriers may be at an increased risk for ICE. Robertsonian translocation homozygosity could be seen as a potential speciation in humans with 44 chromosomes.